Copper-aluminum composite plate strip and production method
By increasing the oxygen content of copper materials and optimizing aluminum treatment, the problem of the reduction of composite strength of copper-aluminum composite plate belt under high-temperature annealing is solved, and low-temperature recrystallization and high-strength copper-aluminum composite plate belt is achieved to meet bending performance and composite Requirements for strength.
Patent Information
- Application Number
- CN202411293771.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-30
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
When the annealing temperature of existing copper-aluminum composite plates is higher than 250℃, the metal compounds between copper-aluminum are increased, resulting in a decrease in the composite strength, making it difficult to meet the requirements of bending performance and composite strength at the same time.
By increasing the oxygen content of the copper material to 50ppm-500ppm, the recrystallization temperature of the copper material is reduced. The copper material with oxygen-enhancing treatment is carried out for oxygen-free high-pressure continuous casting and rolling, combining cold rolling and periodic nitrogen protection cover. Annealing the furnace to produce copper-aluminum composite plate strip.
The complete recrystallization of copper materials is achieved below 300℃, which reduces the heat treatment temperature, reduces the thickness of metal compounds between copper and aluminum, increases the composite strength of copper and aluminum composite plate belt, meets the bending requirements and reduces the energy consumption of the heat treatment process. .
Smart Images

Figure CN119141972A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper-aluminum composite strips, in particular to a copper-aluminum composite strip and a production method. Background Art
[0002] The existing copper-aluminum composite strips have the problem of matching bending and composite strength. In order to meet the bending requirements of copper-aluminum composite strips, the surface hardness of the copper material needs to be soft, tough, high elongation and high annealing temperature. The current annealing temperature is generally around 300°C. When the annealing temperature of the copper-aluminum composite strip is higher than 250°C, the copper-aluminum intermetallic compounds will increase, and will increase sharply when it exceeds 300°C. The thickness of the copper-aluminum composite intermetallic compounds will exceed 2μm, while the recrystallization temperature range of copper is 200-280°C. In order to achieve sufficient recrystallization of copper materials, the recrystallization annealing temperature of copper materials is generally controlled between 380-680°C. Therefore, there is a contradiction between the stable crystallization temperature range of copper materials and the upper temperature limit required for copper-aluminum composite strength.
[0003] The patent with announcement number CN103060624B discloses aluminum materials, copper-aluminum composite strips and processing methods of copper-aluminum composite strips. The copper-aluminum composite strips are composed of an aluminum base layer and a copper coating. The processing steps include forming a blank through oxygen-free high-pressure continuous casting and rolling, and then undergoing cold rolling, intermediate annealing, finishing rolling, and finished product annealing processes. The intermediate annealing temperature of the above technology is 200-400°C, and when the annealing temperature of the copper-aluminum composite strip is higher than 250°C, the copper-aluminum intermetallic compounds will increase, and will increase sharply when it exceeds 300°C, resulting in a thickness of the copper-aluminum intermetallic compounds exceeding 2μm, causing a decrease in composite strength.
[0004] Therefore, there is an urgent need for a copper-aluminum composite plate and strip that can simultaneously meet the requirements of bending performance and composite strength. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the present invention provides a copper-aluminum composite plate and strip and a production method.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A copper-aluminum composite plate strip is composited from aluminum and copper, and is characterized in that the oxygen content of the copper is 50ppm-500ppm.
[0008] Preferably, the oxygen content of the copper material is 50 ppm.
[0009] Preferably, the oxygen content of the copper material is 120 ppm.
[0010] Preferably, the oxygen content of the copper material is 500 ppm.
[0011] A method for producing the above copper-aluminum composite strip, comprising the following steps:
[0012] (1) Red copper or oxygen-free copper is subjected to oxygenation treatment so that the oxygen content of the red copper or oxygen-free copper is 50ppm-500ppm, thereby obtaining a copper material.
[0013] (2) The aluminum ingot is melted at 700-850°C, and Si, Fe, Cu, and Mn are added to melt, refined and degassed, and the molten liquid after refining and degassing is allowed to stand at 690-820°C for 5-15 minutes, and then poured into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material.
[0014] (3) After the copper material of step (1) is subjected to alkaline washing and degreasing treatment, it is single-sided polished until there is no oxide layer on the surface. After polishing, the copper material is heated to 230-250° C.
[0015] (4) The semi-molten aluminum material in step (2) is brought into contact with the polished surface of the copper material in step (3), and oxygen-free high-pressure continuous casting and rolling are performed to obtain a copper-aluminum composite billet.
[0016] (5) The copper-aluminum composite billet of step (4) is subjected to cold rolling treatment, and the total processing rate of the cold rolling treatment is 15-75%.
[0017] (6) The copper-aluminum composite billet after cold rolling in step (5) is subjected to periodic nitrogen protection hood furnace annealing treatment, the room temperature is raised to 170-190° C., purged and degreased for 1.5-2.5 hours, the annealing temperature is 200-300° C., and the temperature is kept for 3-8 hours, and the billet is rapidly cooled to below 65° C. before being taken out of the furnace.
[0018] The beneficial effects of the present invention are as follows: the present invention reduces the recrystallization temperature of the copper material by increasing the oxygen content in the copper material, thereby reducing the annealing temperature. The heat treatment of the copper-aluminum composite billet below 300°C can satisfy the complete recrystallization of the copper material, achieve soft annealing, and meet the bending requirements. At the same time, the thickness of the copper-aluminum intermetallic compound during the heat treatment process is reduced, thereby improving the composite strength of the copper-aluminum composite plate and strip. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0020] Figure 1 is an intermetallic compound thickness diagram of Example 1;
[0021] Figure 2 is a graph of intermetallic compound thickness in Example 2;
[0022] Figure 3 is the intermetallic compound thickness diagram of Example 3;
[0023] Figure 4 is a graph of the thickness of the intermetallic compound of Example 4;
[0024] Figure 5 is a graph of intermetallic compound thickness of Example 5;
[0025] Figure 6 is a graph of intermetallic compound thickness of Example 6;
[0026] Figure 7 is a graph of the thickness of the intermetallic compound of Example 7;
[0027] Figure 8 is a graph of intermetallic compound thickness in comparative example 1;
[0028] Fig. 9 is a graph of intermetallic compound thickness in comparative example 2;
[0029] Fig.10 is a comparative example of the thickness of three intermetallic compounds;
[0030] Fig.11 is a graph of intermetallic compound thickness in comparative example 4;
[0031] Fig.12 is a graph of the thickness of five intermetallic compounds in the comparative example;
[0032] Fig.13 is the thickness diagram of the intermetallic compound in comparative example 6;
[0033] Fig.14 is a graph of intermetallic compound thickness in comparative example 7;
[0034] Fig.15 This is a graph of the intermetallic compound thickness of comparative example eight. DETAILED DESCRIPTION
[0035] In all embodiments of the present invention, unless otherwise specified about temperature and pressure, all are at room temperature and pressure, and unless otherwise specified about the use of equipment, all can be used according to conventional settings.
[0036] To make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific implementation methods. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0037] Combination Figures 1 to 15 :
[0038] Embodiment 1: Figure 1 As shown, a copper-aluminum composite plate and strip is composited from aluminum and copper, the oxygen content of the copper is 120 ppm, and the copper is made from T2 copper through oxygen enrichment treatment.
[0039] Preparation method:
[0040] (1) The T2 copper is subjected to an oxygenation treatment so that the oxygen content of the T2 copper is 120 ppm, thereby obtaining a copper material (the oxygenation treatment method may be, but is not limited to, the oxygenation method disclosed in Publication No. CN116162817A).
[0041] (2) The aluminum ingot is melted at 700°C, and Si, Fe, Cu, and Mn are added to melt and refined and degassed. The molten liquid after refining and degassing is allowed to stand at 790°C for 5 minutes and then poured into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material.
[0042] (3) After the copper material of step (1) is subjected to alkaline washing and degreasing treatment, it is single-sided polished until there is no oxide layer on the surface. After polishing, the copper material is heated to 230° C.
[0043] (4) The semi-molten aluminum material in step (2) is brought into contact with the polished surface of the copper material in step (3) and subjected to oxygen-free high-pressure continuous casting and rolling at a rolling speed of 0.5 m / s and a rolling pressure of 12×10 6 N, to obtain a 6.5 mm copper-aluminum composite billet.
[0044] (5) The copper-aluminum composite billet of step (4) is cold rolled at a rolling speed of 0.5 m / s and a rolling pressure of 20×10 6 N, the tension is 5×10 6 N, the pass processing rate is 10-30%, and the total processing rate is 60%.
[0045] (6) The copper-aluminum composite billet after cold rolling in step (5) is subjected to periodic nitrogen protection hood furnace annealing treatment, the room temperature is raised to 180°C, purged and degreased for 2 hours, the annealing temperature is 250°C, and the temperature is kept for 5 hours. The billet is quickly cooled to below 60°C and taken out of the furnace to obtain a finished product with a thickness of 4 mm.
[0046] Embodiment 2: Figure 2 As shown, the difference from Example 1 is that the thickness of the finished product in step (6) is 3 mm.
[0047] Embodiment 3: Figure 3 As shown, the difference from Example 1 is that the annealing temperature in step (6) is 200°C.
[0048] Embodiment 4: Figure 4 As shown, the difference from Example 2 is that the annealing temperature in step (6) is 200°C.
[0049] Embodiment 5: Figure 5As shown, the difference from Example 1 is that: the oxygen content of the copper material is 180ppm; the oxygen content of the T2 copper in step (1) is 180ppm; the thickness of the composite blank in step (3) is 8mm; and the annealing temperature in step (6) is 230°C.
[0050] Example 6: Figure 6 As shown, the difference from Example 5 is that the thickness of the finished product in step (6) is 3 mm.
[0051] Embodiment 7: Figure 7 As shown, the difference from Example 5 is that the annealing temperature in step (6) is 200°C.
[0052] Example 8: The difference from Example 1 is that: the oxygen content of the copper material is 50ppm; the oxygen content of T2 copper in step (1) is 50ppm; the annealing temperature in step (6) is 210℃, and the holding time is 5 hours. The interface thickness is 600nm and the peel strength is 28N / mm.
[0053] Example 9: The difference from Example 1 is that: the oxygen content of the copper material is 500ppm; the oxygen content of T2 copper in step (1) is 500ppm; the annealing temperature in step (6) is 250℃, and the holding time is 5 hours. The interface thickness is 650nm and the peel strength is 30N / mm.
[0054] Example 10: The difference from Example 1 is that: the oxygen content of the copper material is 60ppm; the oxygen content of the T2 copper in step (1) is 60ppm; the thickness of the composite blank in step (3) is 8mm; the holding time in step (6) is 8 hours. The interface thickness is 600nm and the peel strength is 30N / mm.
[0055] Example 11: The difference from Example 1 is that the thickness of the composite blank in step (3) is 7 mm; the annealing temperature in step (6) is 240°C, the holding time is 6 hours, and the thickness of the finished product is 5 mm. The interface thickness is 500 nm and the peel strength is 35 N / mm.
[0056] Example 12: The difference from Example 1 is that: the oxygen content of the copper material is 200ppm; the oxygen content of the T2 copper in step (1) is 200ppmm; the thickness of the composite blank in step (3) is 8mm; the annealing temperature in step (6) is 220℃, the holding time is 3 hours, and the thickness of the finished product is 3mm. The interface thickness is 500nm and the peel strength is 25N / mm.
[0057] Example 13: The difference from Example 1 is that: the oxygen content of the copper material is 300ppm; the oxygen content of the T2 copper in step (1) is 300ppmm; the thickness of the composite blank in step (3) is 8mm; the annealing temperature in step (6) is 270℃, and the thickness of the finished product is 6mm. The interface thickness is 700nm and the peel strength is 28N / mm.
[0058] Comparative Example 1: Figure 8 As shown, a copper-aluminum composite plate strip is composited from aluminum and copper, and the copper material is T2 copper.
[0059] Preparation method:
[0060] (1) The aluminum ingot is melted at 700°C, and Si, Fe, Cu, and Mn are added to melt, refined and degassed. The molten liquid after refining and degassing is allowed to stand at 790°C for 5 minutes, and then poured into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material.
[0061] (2) After the copper material is treated with alkaline washing and degreasing, it is single-sided polished until there is no oxide layer on the surface. After polishing, the copper material is heated to 230°C.
[0062] (3) The semi-molten aluminum material in step (1) is brought into contact with the polished surface of the copper material in step (2) and subjected to oxygen-free high-pressure continuous casting and rolling at a rolling speed of 0.5 m / s and a rolling pressure of 12×10 6 N, to obtain a 6.5 mm copper-aluminum composite billet.
[0063] (4) The copper-aluminum composite billet of step (3) is cold rolled at a rolling speed of 0.5 m / s and a rolling pressure of 20×10 6 N, the tension is 5×10 6 N, the pass processing rate is 10-30%, and the total processing rate is 60%.
[0064] (5) The copper-aluminum composite billet after cold rolling in step (4) is subjected to periodic nitrogen protection hood furnace annealing treatment, the room temperature is raised to 180°C, purged and degreased for 2 hours, the annealing temperature is 250°C, and the temperature is kept for 5 hours. The billet is quickly cooled to below 60°C and taken out of the furnace to obtain a finished product with a thickness of 4 mm.
[0065] Comparative Example 2: Fig. 9 As shown, the difference from Comparative Example 1 is that the thickness of the finished product in step (5) is 3 mm.
[0066] Comparative Example 3: Fig.10 As shown, the difference from Comparative Example 1 is that the annealing temperature in step (5) is 315° C. and the holding time is 8 hours.
[0067] Comparative Example 4: Fig.11 As shown, the difference from Comparative Example 3 is that the thickness of the finished product in step (5) is 3 mm.
[0068] Comparative Example 5: Fig.12 As shown, the difference from Comparative Example 3 is that the thickness of the composite blank in step (3) is 8 mm.
[0069] Comparative Example 6: Fig.13 As shown, the difference from Comparative Example 5 is that the thickness of the finished product in step (5) is 3 mm.
[0070] Comparative Example 7: Fig.14 As shown, the difference from comparative example 1 is that the thickness of the composite blank in step (3) is 8 mm; and the annealing temperature in step (5) is 230°C.
[0071] Comparative Example 8: Fig.15 As shown, the difference from Comparative Example 7 is that the thickness of the finished product in step (5) is 3 mm.
[0072] Relevant performance tests were conducted on Examples 1 to 7 and all comparative examples, as shown in the following table for details:
[0073]
[0074]
[0075]
[0076] It can be fully seen from the above data that, compared with traditional oxygen-free copper, the present invention reduces the recrystallization temperature of the copper material by increasing the oxygen content in the copper material, thereby reducing the annealing temperature in the heat treatment. The heat treatment of the copper-aluminum composite billet below 300°C can meet the complete recrystallization of the copper material. The annealing temperature is low, the energy consumption is low, the process is stable, and soft annealing is achieved to meet the bending requirements. At the same time, the thickness of the copper-aluminum metal compound during the heat treatment process is reduced, the copper-aluminum composite interface layer is controlled below 1μ, and the composite strength of the copper-aluminum composite plate and strip is increased from the traditional 12N / mm to more than 20N / mm.
[0077] The above implementation modes cannot limit the protection scope of the invention. Without departing from the spirit and scope of the invention, the invention may have various changes and improvements, and these changes and improvements all fall within the scope of the invention claimed for protection.
Claims
1. A copper-aluminum composite plate and strip, which is composed of aluminum and copper, characterized in that: The oxygen content of the copper material is 50ppm-500ppm.
2. The copper-aluminum composite strip according to claim 1, characterized in that: The oxygen content of the copper material is 50 ppm.
3. The copper-aluminum composite strip according to claim 1, characterized in that: The oxygen content of the copper material is 120 ppm.
4. The copper-aluminum composite strip according to claim 1, characterized in that: The oxygen content of the copper material is 500 ppm.
5. A method for producing the copper-aluminum composite strip according to claim 1, characterized in that: Here are the steps: (1) subjecting red copper or oxygen-free copper to an oxygen-enhancing treatment so that the oxygen content of the red copper or oxygen-free copper is 50 ppm to 500 ppm, thereby obtaining a copper material; (2) melting the aluminum ingot at 700-850°C, adding Si, Fe, Cu, and Mn to melt, refining and degassing, letting the refined and degassed molten liquid stand at 690-820°C for 5-15 minutes, and then pouring it into a preheated casting nozzle. The cast aluminum alloy liquid is cooled and crystallized to a semi-molten state to obtain a semi-molten aluminum material; (3) After the copper material of step (1) is subjected to alkaline washing and degreasing treatment, it is single-sided polished until there is no oxide layer on the surface, and the copper material is heated to 230-250° C. after polishing; (4) placing the semi-molten aluminum material in step (2) in contact with the polished surface of the copper material in step (3), and performing oxygen-free high-pressure continuous casting and rolling to obtain a copper-aluminum composite billet; (5) cold rolling the copper-aluminum composite billet of step (4), wherein the total processing rate of the cold rolling process is 15 to 75%; (6) The copper-aluminum composite billet after cold rolling in step (5) is subjected to periodic nitrogen protection hood furnace annealing treatment, the room temperature is raised to 170-190° C., purged and degreased for 1.5-2.5 hours, the annealing temperature is 200-300° C., and the temperature is kept for 3-8 hours, and the billet is rapidly cooled to below 65° C. before being taken out of the furnace.
Citation Information
Patent Citations
Aluminum substrate material of copper-aluminum composite plate strip, copper-aluminum composite plate strip and processing method of copper-aluminum composite plate strip
CN103060624A
Rolled copper foil manufacturing method and rolled copper foil
CN115921571A
Preparation method of red copper cast ingot
CN116162817A
Rolled copper foil as base plate for making flexible printed circuit board and its production method
CN1254251A
Rolled copper foil
JP2010150597A
